Pengaruh Prestasi Kerja dan Loyalitas Kerja Terhadap Promosi Jabatan Karyawan pada Direktorat SDM PT Krakatau Bandar Samudera - Siti Salma Nurul Huda; Hero Wirasmara Kusuma; Enji Azizi (JURNAL RISET MANAJEMEN (JURMA), 2024)
This research aims to determine the influence of work performance and monkey loyalty on job promotion at the HR Directorate of PT Krakatau Bandar Samudera. The influence you want to know is partial and simultaneous (together). This type of research is a saturated sample that explains the influence between variables through hypothesis testing. This research used a sample of 50 respondents. The sample in this research was determined through Non Probability Sampling using the characteristics of respondents and employee performance at the company. The test tool used is SPSS version 27, including the tests analyzed, namely regression analysis, T test, F test. From the results of this test it can be concluded that the influence of work performance and loyalty has a partial and simultaneous (together) effect on employee promotion at HR Directorate of PT Krakatau Bandar Samudera.